PENGARUH PEMBERIAN BERBAGAI JENIS PUPUK ORGANIK TERHADAP PERTUMBUHAN VEGETATIF TANAMAN BUAH NAGA (Hylocerios costaricensis) - Djaya, Muhammad Syarif; Ni'mah, Gusti Khairun (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
The aim of this research was to determine the effect of various types of organic fertilizer on the vegetative growth of dragon fruit. The research used an experiment using the Completely Randomized Design method with four treatments A1 = Goat Manure, A2 = Cow Manure, A3 = Guano Fertilizer, A4 = Chicken Manure with four replications. The results of the research showed that the application of various kinds of organic fertilizer had a very significant effect on plant height and a significant effect on the number of branches of dragon fruit plants. Providing organic fertilizer, namely guano fertilizer and chicken manure, can provide higher plant height and a greater number of branches. It is thought that the high content of macro nutrients N, P and K can increase the vegetative growth of dragon fruit plants